Bit error floor of multi‐level phase modulation with noisy phase reference. Issue 13 (1st June 2017) - Lee, J.; Jang, Y.; Yoon, D.
Abstract : A simple method is proposed for the derivation of bit error floor (BEF) expressions of multi‐level phase modulations with noisy phase reference based on the geometric features of constellations. To validate the result, average BEF expressions of 8 + 8 and 4 + 12 amplitude and phase‐shift keyings adopted in digital video broadcasting‐satellite 2 extensions are derived and consultative committee for space data systems, and analyse the results.